Aktivitas Antirayap Ekstrak Daun Pepaya dan Kumis Kucing (Antitermite Activities of Leaf Extracts of Pepaya and Kumis Kucing) - Abdul Azis; Tibertius A Prayitno; Ganis Lukmandaru; Tomy Listyanto (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Antitermite activities of leaf hexane extract of cat whiskers (Orthosiphon sp.) leaves, ethyl acetate, and ethanol- toluene extracts of pepaya (Carica sp.) leaves were investigated in several concentrations (1, 5, 10, and 15%, weight based) that be impregnated to filter papers againts the dry-wood termites Cryptotermes sp. After impregnation, filter papers were dried into oven at 60 °C for 3 hours, then were tested to termites for 4 weeks. The results showed that treatment concentration could obtain the highest termites mortality level, no weight loss and the lowest damage level. Ethyl acetate extract of papaya leaves exhibited the highest termites mortality (91.2%) at concentration of 10%. This concentration also showed the lowest weight loss (0%) and the highest antifeedant activity (antifeedant coefficient of 100%). Ethyl acetate extract of papaya leaves exhibited the lowest of LC50 value (7844.20 μg ml-1 ). Antitermitic activity showed a trend more repellent than toxic. Fatty acid such as hexadecanoic acid, linolenic acid, octadecanoic acid and steroid compounds that detected by GC-MS were estimated to play a role as antitermite agents. Thus, the application of ethyl acetate extract of papaya leaves at concentration of 10% was recommended to the next experiment by using solid wood impregnation.